Analisis Verba Gerak Bahasa Jepang (Idoudoushi) Tooru dan Sugiru - Iin Kusmiati; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis study discusses the meaning of Japanese verbs of motion or idoudoushi. The background of this study is the chosen title for sugiru verb and tooru verb often used in Japanese leasson and two verbs that have similar meanings is past, so that confusing its use in a sentence for Japanese learners.The method used in this study is descriptive method. The data is taken from the dictionary Koujien by Izuru, Shinmura (1991). The results of this study indicate that there are differences and similarities between sugiru verb and tooru verb.Keywords: idoudoushi, lexical meaning, meaning expansion